The break up of Commonwealth private international law in relation to forum non conveniens and tort choice of law in selected Commonwealth jurisdictions - Tong, William Su Hern (2007)
It is well known that in the early stages of legal development in Commonwealth jurisdictions, when these countries were still colonies of the British Empire, there was uniformity in their laws as the English common law was received by these countries and applied by their judiciaries with little or no modifications. As time passed, with the shift towards independence in these former British colonies, some Commonwealth countries have diverged from the English common law by providing for judicial solutions that are perceived to best fit their individual circumstances, values and needs. In other words, there has been a break up of Commonwealth common law. Whilst there has been much academic discussion on this phenomenon in relation to for example, tort and contract, hardly any has been written on private international law. Accordingly, it is the purpose of this thesis to address the paucity of academic writing on this subject matter by undertaking a comparative study of two areas of private international law, namely the doctrine of forum non conveniens and tort choice of law in Australia, Canada and Singapore, with the relevant English common law positions as the key reference point. Specifically, this thesis began by establishing the existence as well as the nature and extent of the break up of forum non conveniens and tort choice of law in our selected Commonwealth jurisdictions. It is then argued that one reason for this phenomenon is that there are differences in the judicial treatment of policies, concepts and other wider considerations relevant to these areas of private international law in these countries. Subsequently, the issue of how these jurisdictions should respond to this phenomenon was examined and we concluded that the prospects for the harmonisation of jurisdictional and tort choice of law rules at the global, regional and Commonwealth level has been largely unpromising. Accordingly, it is argued that the way forward is for our selected Commonwealth jurisdictions to develop their own rules on these areas of private international law with their own social, economic and political circumstances in mind.